World record 32.35 tesla direct-current magnetic field generated with an all-superconducting magnet - Liu, Jianhua; Wang, Qiuliang; Qin, Lang; Zhou, Benzhe; Wang, Kangshuai; Wang, Yaohui; Wang, Lei; Zhang, Zili; Dai, Yinming; Liu, Hui; Hu, Xinning; Wang, Hui; et al. (Superconductor science & technology, 2020)
We have successfully reached the world record 32.35 T direct-current magnetic field by using a homemade all-superconducting magnet. The magnet has consisted of a 15 T low temperature superconductor outsert coil and two high temperature superconductor no-insulation (NI) insert coils using a conductor tape coated of REBCO (REBa2Cu3Ox, where RE = Y, Gd). This result proves the feasibility of reaching a strong magnetic field up to 32 T by using the NI process as well as the superconductor magnet with insulation. This magnet is one of the essential parts of the 'Synergetic Extreme Condition User Facility' project, which provides expertize, instrumentation, and infrastructure for investigating matter science under extreme physical conditions. We thought that such a strong superconductor magnet would bring the possibility to explore more mystery in physics, medicine, pharmacy, etc.